Comparative Effects of Datura stramonium Leaf and Seed Extracts on Membrane Stabilization and Platelet Aggregation In-vitro (African Journal of Biomedical Research, 2019)
Despite the progress in developing new therapies, inflammatory diseases remain one of the major causes of mortality. In this study, anti-inflammatory activity of the aqueous extracts of Datura stramonium leaves and seeds were evaluated. Heat and hypotonicity-induced haemolysis of human red blood cells (HRBCs) were used to determine the effect of the extracts on membrane stabilization, and the effect of the extracts on platelet aggregation was determined using calcium chloride (CaCl2)-induced platelet aggregation. The concentrations of the extracts used were 0.1, 0.2, 0.4, 0.6 and 0.8 mg/ml. Indomethacin (0.4 mg/ml) was used as the standard drug. The leaf extract significantly (p < 0.05) inhibited heat-induced haemolysis by 44.47% and 52.89% at 0.2 and 0.1 mg/ml respectively compared to the seed extract. On the other hand, the seed extract significantly (p < 0.05) inhibited heat-induced haemolysis by 29.5%, 44.88% and 50.01% at 0.4, 0.6 and 0.8 mg/ml respectively compared to the leaf extract. Effect of the leaf extract on hypotonicity-induced haemolysis showed that it significantly (p < 0.05) inhibited haemolysis from 27.27% - 68.67% corresponding to concentrations 0.1 – 0.8 mg/ml, compared to the seed extract. The effect of the extracts on platelet aggregation showed that the leaf extract exhibited significantly (p < 0.05) higher inhibition of platelet aggregation from 0 – 120 seconds, compared to the seed. Both extracts thus, have comparable effect on heat-induced haemolysis of HRBCs, though at different concentrations. The ability of the leaf extract to inhibit hypotonicity-induced haemolysis and platelet aggregation outweigh that of the seed.
Keywords: Anti-inflammatory; heat-induced haemolysis; hypotonicity-induced haemolysis; platelet aggregation; Datura stramonium